Augmentation of NKT and NK cell-mediated cytotoxicity by peptidoglycan monomer linked with zinc. Issue 2 (2002) - Mrakovčić-Šutić, Ines; Radošević-Stašić, Biserka; Šimin, Marija; Muhvić, Damir; Rukavina, Daniel
Abstract : Background : Peptidoglycan monomer (PGM), which was originally prepared by biosynthesis from culture fluids of penicillin-treated Brevibacterium divaricatum, is an immunostimulator, the activities of which might be improved by addition of zinc (Zn) to the basic molecule. Methods : To test the possible cytotoxic effects of this new analogue, we analyzed the ability of PGM-Zn and PGM to change the phenotypic profile of hepatic and splenic mononuclear lymphatic cells and to affect the growth of malignant T-cell line YAC-1 and syngeneic thymocytes. Results : Pretreatment of C57BL/6 mice primarily with PGM-Zn over 6 days (10/mg/kg intraperitoneally) significantly enhanced the proportions of NK1.1 high+, CD4 - CD8 -, CD69 +, and CD3 intermediate /NK1.1 + /IL2R-β + (NKT) cells in the liver, and major histocompatibility complex class II +, CD69 +, and CD8 + cells in the spleen. Both types of cells were highly cytotoxic against YAC-1 and syngeneic thymocytes, increasing the destruction of YAC-1 by 70% on addition of hepatic cells and by 30% on addition of splenic cells. Destruction of thymocytes increased by 10 and 50%, respectively. Conclusion : The results point to PGM-Zn as a potent cytotoxicity-inducing agent, which also generates autoreactive NKT cells.